The developmental trajectories of the behavioral phenotype and neuropsychiatric functioning in Cornelia de Lange and Rubinstein Taybi syndromes: A longitudinal study. Issue 2 (14th November 2022) - Ajmone, Paola Francesca; Giani, Ludovica; Allegri, Beatrice; Michelini, Giovanni; Dall'Ara, Francesca; Rigamonti, Claudia; Monti, Federico; Vizziello, Paola Giovanna; Selicorni, Angelo; Milani, Donatella; Scaini, Simona; Costantino, Antonella
Abstract: Several changes in the behavioral phenotype arise with the growth of children affected by Cornelia de Lange Syndrome (CdLS) and Rubinstein‐Taybi Syndrome (RSTS). However, previous research relied on a cross‐sectional study design turning into age‐related comparisons of different syndromic cohorts to explore age‐dependent changes. We aim to outline the variating pathways of the neuropsychiatric functioning across the lifespan in CdLS and RSTS, through the setting up of a longitudinal study design. The sample included 14 patients with CdLS and 15 with RSTS. The assessments were carried out in two different timepoints. Our findings highlight that the cognitive profile of CdLS is subjected to a worsening trend with decreasing Intellectual Quotient (IQ) scores from T0 to T1, whereas RSTS shows a stable IQ over time. Patients affected by RSTS show greater improvements compared to CdLS in communication, daily living skills, social abilities, and motor skills across the lifespan. Both syndromes report an upward trend in behavioral and emotional difficulties even if CdLS exhibit a significant and major deterioration compared to individuals with RSTS. Being aware of the early dysfunctional patterns which might pave the way for later neuropsychiatric impairments is the first step for planning preventive interventions.